2021
DOI: 10.21203/rs.3.rs-491688/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infections among neonates born to women with SARS-CoV-2 infection: maternal, pregnancy and birth characteristics

Abstract: Among 10,011 neonates of SARS-CoV-2-infected mothers, 1448 (14%) underwent PCR testing (and 1347 (95%) had mothers with third trimester infections). Fifty-nine (4%) were PCR-positive. Neonates testing positive were born to both symptomatic and asymptomatic women, and nearly all were born to women with infection identified near delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated infants rooming in with mother encourages initiation of the infant being fed breastmilk, and rooming-in is recommended by numerous public health and clinical organizations to support breastfeeding [1,16,17,18,19]. While early recommendations included consideration for temporary separation of mothers with COVID-19 from their newborns, multiple studies have now found low incidence of SARS-CoV-2 infection among infants born to people with SARS-CoV-2 infection [20] and low risk of transmission from mother to infant when appropriate IPC is followed [21]. The AAP and CDC recommend that mothers with COVID-19 room-in with their infants and use appropriate IPC measures (e.g., masks, hand hygiene) even if asymptomatic [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated infants rooming in with mother encourages initiation of the infant being fed breastmilk, and rooming-in is recommended by numerous public health and clinical organizations to support breastfeeding [1,16,17,18,19]. While early recommendations included consideration for temporary separation of mothers with COVID-19 from their newborns, multiple studies have now found low incidence of SARS-CoV-2 infection among infants born to people with SARS-CoV-2 infection [20] and low risk of transmission from mother to infant when appropriate IPC is followed [21]. The AAP and CDC recommend that mothers with COVID-19 room-in with their infants and use appropriate IPC measures (e.g., masks, hand hygiene) even if asymptomatic [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…expansion and availability of COVID-19-related data, additional studies appeared reporting adverse perinatal outcomes associated with SARS-CoV-2 infection during pregnancy comprising an increased risk of maternal ICU admission, cesarean delivery, preterm birth, and congenital anomalies among other effects. [9][10][11][12] Meanwhile, early epidemiologic data from the pandemic revealed that African Americans, Native Americans, and Hispanics were disproportionately impacted by the pandemic, marked by elevated rates of SARS-CoV-2 infection and heightened risk of adverse COVID-19 related outcomes including mortality in these populations. [13][14][15][16] Over the past two decades similar racial and ethnic disparities have been observed in several pregnancyrelated outcomes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%